2023
DOI: 10.3389/fendo.2023.1192113
|View full text |Cite
|
Sign up to set email alerts
|

Association between neutrophil to lymphocyte ratio and erectile dysfunction among US males: a population-based cross-sectional study

Abstract: ObjectiveThe purpose of the study was to investigate the relationship between neutrophil-to-lymphocyte ratio (NLR) and erectile dysfunction (ED) in adult American males using a large database.MethodsWe adopted a series of statistical analyses of the relationship between NLR indices and ED prevalence among participants in the 2001-2004 National Health and Nutrition Examination Survey (NHANES) database using the R software.ResultsThe study included a total of 3012 participants, of whom 570 (18.9%) presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 27 , 28 Another study also showed that MHR can be used as an independent predictor of response to phosphodiesterase 5 inhibitor therapy for ED. 47 However, these studies on MHR and ED had small sample sizes and insufficient evidence, so this study used nationally representative data from NHANES to build on the available evidence.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Another study also showed that MHR can be used as an independent predictor of response to phosphodiesterase 5 inhibitor therapy for ED. 47 However, these studies on MHR and ED had small sample sizes and insufficient evidence, so this study used nationally representative data from NHANES to build on the available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Coulter counter method, we obtained the neutrophil count (NC) and lymphocyte count (LC) from the whole blood. The ratio of NC to LC was then used to calculate the NLR ( 19 ). We also looked at the associations between DKD and other inflammatory markers, such as the platelet-to-lymphocyte ratio (PLR) (PLR= platelet count(PC)/LC), monocyte-to-lymphocyte ratio (MLR) (MLR= monocyte count(MC)/LC), systemic immune-inflammation index (SII) (SII=PC * NC/LC), system inflammation response index (SIRI) (SIRI=NC * MC/LC), and aggregate index of systemic inflammation (AISI) (AISI=NC * PC * MC/LC), to fully assess the relationship between NLR and DKD.…”
Section: Methodsmentioning
confidence: 99%